The Feasibility of Eco-Bricks as Recycled Products in Yogyakarta Waste Bank - Astuti, Amalia Yuli; Setiawan, Darma Putra; Fitriani, Syifa (School of Industrial and System Engineering, Telkom University, 2025)
Plastic waste is an inorganic waste that can pollute the environment and is difficult to decompose. Recycling of plastic waste has not been widely used because the selling price is not too high. So, plastic waste is simply thrown away then ends up in the landfill and reducing soil fertility. Eco-brick is the product solution for plastic waste management. The Kamulyan waste bank searched to accommodate and reuse plastic waste into eco-bricks which greatly assists the management of plastic waste in Yogyakarta. This research was conducted to determine the economic feasibility of the eco-bricks as the product of recycling activity. The research method used the Benefit-Cost Ratio (BCR), Net Present Value (NPV), and Internal Rate of Return (IRR) for analyzing the economic feasibility of investment activities carried out by the Kamulyan Waste Bank. The results were feasible for NPV with positive values at Rp 1.331.313 and 9,32% as the rate of return for IRR. The BCR was not feasible cause the BCR was lower than the standard value. Recycling activities provide direct benefits in the form of net profit derived from the sale of recycled products of Rp 1.741.421 from 2020 to 2021. The indirect benefits were being able to reduce the accumulation of plastic waste PET bottles and sachets in Yogyakarta by 0.008% and reducing plastic waste management costs of Rp 1.069.636,84.